An observer-based control of linear systems with uncertain parameters via LMI approach - Hiba Hizazi; Mustapha Lhous; El Mostafa Magri; Ayoub Sakkoum (Archives of Control Sciences, 2025)
In this paper, the Linear Matrix Inequality (LMI) method is used to solve the problem of making observer-based control solutions for a class of uncertain linear systems. The study yields both control and observer gains derived from feasible LMI solutions. To illustrate the effectiveness of our approach, we present a practical example, showcasing the practicality and applicability of the proposed solutions.